Kesempurnaan Cinta dan Tipe Kepribadian Kode Warna - Setiawan, Yamin (Persona:Jurnal Psikologi Indonesia, 2014)
Abstract. This research that relates consummate love with the colour-coded personalities: red, blue, white and yellow developed by Taylor Hartman (2004). As the new improvement, this research aims at discovering if there are any differences of consummate love between individuals with the personalities red, blue, white and yellow. The samples of this research are 77 unmarried man and woman. The instrument that is used for getting the subjects' differences type of personalities is the colour-coded personalities scale. Meanwhile, likert scale is used to reveal the level of the consummate love of the subjects. The collected data is analyzed with the 'one-way analysis of variance technique'. The findings of this research show that there are significant differences of consummate love observed from the colour-coded personalities.Keywords : Consummate Love, types of colour-coded personality